Foreign investment of US multinationals: The effect of tax policy and agency conflicts. - Albertus, James F.; Glover, Brent; Levine, Oliver (Journal of Financial Economics, 2022)
We estimate a dynamic model, featuring agency conflicts and a stochastic tax reform arrival, to evaluate how the change from a worldwide to territorial tax system, enacted under the Tax Cuts and Jobs Act (TCJA), affects foreign investment. Although a worldwide system imposes a higher tax liability on foreign income, we show it encourages excess foreign investment by depressing the opportunity cost of capital. In our estimated model, the TCJA reduces foreign investment by 15.6% on average, with larger declines for services firms and firms with lesser agency conflicts. The reform probability, which we estimate in the model, significantly affects firms’ investment and cash holdings.